Thermoelectric Nanostructures: From Physical Model Systems towards Nanograined Composites - Nielsch, Kornelius; Bachmann, Julien; Kimling, Johannes; Boettner, Harald (Advanced Energy Materials, 2011)
Thermoelectric materials could play an increasing role for the efficient use of energy resources and waste heat recovery in the future. The thermoelectric efficiency of materials is described by the figure of merit ZT = (S-2 sigma T)/kappa (S Seebeck coefficient, sigma electrical conductivity,. thermal conductivity, and T absolute temperature). In recent years, several groups worldwide have been able to experimentally prove the enhancement of the thermoelectric efficiency by reduction of the thermal conductivity due to phonon blocking at nanostructured interfaces. This review addresses recent developments from thermoelectric model systems, e. g. nanowires, nanoscale meshes, and thermionic superlattices, up to nanograined bulk-materials. In particular, the progress of nanostructured silicon and related alloys as an emerging material in thermoelectrics is emphasized. Scalable synthesis approaches of high-performance thermoelectrics for high-temperature applications is discussed at the end.